PENGEMBANGAN MEDIA INTERAKTIF PEMBELAJARAN COMPUTATIONAL THINKING “JEJAKLOGIKA” UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP - Adipura, Laksamana; Handayani, Anik; Srini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Computational Thinking (CT) is a fundamental problem-solving approach in the digital era, involving skills such as decomposition, pattern recognition, abstraction, and algorithmic thinking. This study aims to develop an interactive learning media called JejakLogika, designed to enhance junior high school students’ critical thinking skills through the CT approach. The research employed a Research and Development (R&D) methodology using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and was conducted with seventh-grade students at SMPN 22 Malang. Validation results indicated that the learning media received an "excellent" rating from subject matter experts (92%), media experts (94%), and small-scale trial users (84%). The JejakLogika interactive media successfully integrates CT skills within a web-based platform featuring educational games such as Match Up, Group Sort, Whack-a-Mole, and Rank Order. The findings suggest that this learning media fosters an interactive and engaging learning environment, while simultaneously increasing students' motivation and interest in CT content. JejakLogika can be implemented as an alternative solution to address the low critical thinking skills among junior high school students and the challenges teachers face in integrating CT concepts into classroom instruction.